Ditadura e gênero: mulheres no movimento estudantil paranaense (1964-1985) - Borges, Luana Regina (2020)
This research is linked to the History of Education field and investigates the engagement of women in the university student movement, at União Paranaense dos Estudantes (UPE) (Student Union of Parana), during the period of the civil-military dictatorship (1964-1985), from a gender perspective. We analyze the documents produced by the Department of Political and Social Order (DOPS) during the dictatorship to point out the active and political women‟s participation during this period. The sources are divided into thematic and individual folders. For didactic purposes, we first investigated how the student movement in Brazil and Paraná was organized to gather information about its struggles and the socio-cultural context around it. Next, we discuss gender theory, with the dialogue between the studies of Michelle Perrot, a scholar in the field of women's history who researches the historical (in)visibility of women, and Joan Wallach Scott, an historian whose work seeks a deep understanding of the women‟s history from a gender perspective. Then, militant women are presented the way they appear in the DOPS-PR Thematic Folders. In the third chapter, we carry out an analysis of the dictatorial period, based on the historiography produced by classical authors such as Thomas Skidmore and Maria Helena Moreira Alves, who help us to reflect on the coup and the subsequent Brazilian political/social reality. Authors, such as Joana Maria Pedro and Ana Maria Colling, discuss women‟s militancy and address this issue regarding the dictatorial context. The investigation of the sources related to female militancy in the context of the Paraná student movement and the authoritarian state is in the last two chapters. Finally, it was possible to find women's militancy in the student movement of Paraná through the Folders analyzed, indicating an active participation in this political/educational movement, especially after 1975, the International Women‟s Year.